2005
DOI: 10.1007/s00429-005-0457-y
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy, histology, histochemistry and fine structure of the Harderian gland in the South American armadillo Chaetophractus villosus (Xenarthra, Mammalia)

Abstract: The anatomical, histological, histochemical and ultrastructural characteristics of the Harderian gland of the armadillo Chaetophractus villosus were described. The gland is the largest structure in the bony orbit. It is situated in the anteroventral region of the orbit. Obvious structural differences are not observed between males and females. The gland is compound-branched tubulo-alveolar, being characterized by a single layer of columnar cells surrounded by myoepithelial cells. It possesses a single excretor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 48 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…The number of secretory ducts of the AOG varies within tetrapods (Rehorek et al, ). A single exiting duct has been described for a variety of tetrapods, including rodents (Payne et al, ; Shirama and Hokano, ; Theissen, ; Djeridane, ; this study), rabbits (Rehorek et al, 2011), deer (Rehorek et al, ), tree shrews (Pradidarcheep et al, ), armadillos (Weaker, ; Aldana Marcos and Affani, ), opossums (Krause and McMenamin, ), birds (Burns, ), and frogs (Chieffi et al, ). However, multiple exiting ducts have been described in dolphins (Tarpley and Ridgway, ) and reptiles (Saint‐Girons, ).…”
Section: Discussion—specifics Of the Systemmentioning
confidence: 61%
“…The number of secretory ducts of the AOG varies within tetrapods (Rehorek et al, ). A single exiting duct has been described for a variety of tetrapods, including rodents (Payne et al, ; Shirama and Hokano, ; Theissen, ; Djeridane, ; this study), rabbits (Rehorek et al, 2011), deer (Rehorek et al, ), tree shrews (Pradidarcheep et al, ), armadillos (Weaker, ; Aldana Marcos and Affani, ), opossums (Krause and McMenamin, ), birds (Burns, ), and frogs (Chieffi et al, ). However, multiple exiting ducts have been described in dolphins (Tarpley and Ridgway, ) and reptiles (Saint‐Girons, ).…”
Section: Discussion—specifics Of the Systemmentioning
confidence: 61%
“…Because there are a few study about the eye anatomy in the sloth, we compared our results with American armadillo Chaetophractus villosus . According to Aldana Marcos and Affani (2005), the lacrimal and superficial gland of the third eyelid in the South American Armadillo histologically and histochemically was identical because of the type of cells of the secretory endpieces (mucous, seromucous and serous cells). Our study, as well as the study in armadillos (Aldana Marcos, 1996; Aldana Marcos & Affani, 2005; Aldana Marcos et al, 1995, 2002; Cavagnari et al, 2001; Cavangnari et al, 1988; Weaker, 1981), confirms the presence of the deep gland of the third eyelid, what was opposite to the results obtained in the brown‐throated sloth by Sena et al (2021).…”
Section: Discussionmentioning
confidence: 99%
“…The association between spherical lenses and fossorial habits in frogs is distinct from what has been observed in some fossorial mammals such as the South American armadillo ( Chaetophractus villosus ), which appears to have flattened lenses [46]. However, previous work has shown that fossorial adult caecilian amphibians (Gymnophonia) with aquatic larvae have only slightly flattened lenses as adults [47].…”
Section: Discussionmentioning
confidence: 99%